2003
DOI: 10.1080/00288330.2003.9517164
|View full text |Cite
|
Sign up to set email alerts
|

Importance of different size classes of phytoplankton in Beatrix Bay, Marlborough Sounds, New Zealand, and the potential implications for the aquaculture of the mussel,Perna canaliculus

Abstract: Phytoplankton are recognised as the primary source of food for cultured mussels. Small phytoplankton (<5 µm), however, are often not efficiently retained as food and therefore phytoplankton size can affect bivalve growth and condition. In Beatrix Bay, New Zealand, small picophytoplankton (phytoplankton <2 µm in diam.) sized cells contributed on average 29% of the phytoplankton biomass. They dominated the biomass (52%) in June (winter), when light was limiting, and (40%) during September (spring), when light le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…It is now well established that many bivalves are unable to efficiently remove cells in the picoplankton size range (Widdows et al 1979, Dupuy et al 1999, Tomaru et al 2002. In 1999, studies conducted in Beatrix Bay, Pelorus Sound, in summer found that picophytoplankton (> 0.2 to 2 mm) in the top 15 m of the water column comprised on average 29% of the phytoplankton biomass but contributed, at times, up to 65% (Safi & Gibbs 2003). Consequently the size class structure of phytoplankton in Pelorus Sound may have significant implications for the sustainability of mussel aquaculture in this area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now well established that many bivalves are unable to efficiently remove cells in the picoplankton size range (Widdows et al 1979, Dupuy et al 1999, Tomaru et al 2002. In 1999, studies conducted in Beatrix Bay, Pelorus Sound, in summer found that picophytoplankton (> 0.2 to 2 mm) in the top 15 m of the water column comprised on average 29% of the phytoplankton biomass but contributed, at times, up to 65% (Safi & Gibbs 2003). Consequently the size class structure of phytoplankton in Pelorus Sound may have significant implications for the sustainability of mussel aquaculture in this area.…”
Section: Introductionmentioning
confidence: 99%
“…If Perna canaliculus are unable to efficiently remove picophytoplankton, then a significant amount of biomass in marine farms in parts of the Pelorus Sound may not be available for grazing (Safi & Gibbs 2003). One aim of the present study was to establish whether the picophytoplankton are being efficiently removed by P. canaliculus or whether P. canaliculus supplement their diet, as other bivalves do, through the consumption of heterotrophic food sources such as microzooplankton (Dupuy et al 1999, Wong et al 2003) and bacteria (Pile & Young 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Most suspended biomass was not in living cells, similar to Skidaway River Estuary, USA, where most suspended material was detrital (Verity 2002). Although picophytoplankton were uncounted here, they contribute only an average of 29% to phytoplankton C in central Pelorus Sound (Safi & Gibbs 2003). Furthermore, mesozooplankton enumerated in Beatrix Bay in October 1997 to October 1999 contributed only an average of 2 mg N m -3 to suspended PN (J. R. Zeldis unpubl.…”
Section: Seston Composition Dynamics and Ecological Rolementioning
confidence: 99%
“…Most suspended biomass was not in living cells, similar to Skidaway River Estuary, USA, where most suspended material was detrital (Verity 2002). Although picophytoplankton were uncounted here, they contribute only an average of 29% to phytoplankton C in central Pelorus Sound (Safi & Gibbs 2003). ; Fig.…”
mentioning
confidence: 99%
“…Monthly mean SST was ob tained using AVHRR satellite radiometer data (NIWA SST Archive, NSA: Uddstrom & Oien 1999) Zeldis et al (2008). Total microphytoplankton carbon biomass was calculated as the sum of these taxa and ac counted for an average of 71% of total phytoplankton carbon (Safi & Gibbs 2003).…”
Section: Environmental Settingmentioning
confidence: 99%